ANALISIS PERAN INTERMEDIASI PERBANKAN DI INDONESIA PADA TAHUN 2004-2008 - Widiantini, Astri (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2010)
This Research is to know influence of CAR, NPL, Rate Of Interest of SBI to Ability Of Monetary Intermediasi (LDR) and to know most variable influence of LDR. Analysis method which used in this research quantitative descriptive method by using statistical analysis that is analysis of regresi doubled linear, Statistical test and classic assumption test. From result of research indicate that NPL have more influence signifikan to LDR compared to CAR and of SBI. Because NPL influence to amount of channeling of banking credit. Pursuant to conclusion above, expected banking earn more optimal its function him by taking care of storey;level assess CAR, lessening location of fund SBI as well as more selective again channeling of credit value of NPL remain to lower